Dynamics of Fluid Fuel Reactors in the Presence of Periodic Perturbations. (11th December 2007) - Dulla, S.; Nicolino, C.
Abstract : The appearance of perturbations characterized by a periodic time behavior in fluid fuel reactors is connected to the possible precipitation of fissile compounds which are moved within the primary circuit by the fuel motion. In this paper the time-dependent response of a critical fluid fuel system to periodic perturbations is analyzed, solving the full neutronic model and comparing the results with approximate methods, such as point kinetics. A fundamental eigenvalue of the problem is defined, characterizing the trend of divergence of the power. Parametric studies on the reactivity insertion, the fuel velocity and the recirculation time are performed, evidencing the sensitivity of the eigenvalue on typical design parameters. Non-linear calculations in the presence of a negative feedback term are then performed, in order to assess the possibility to control a fluid fuel system when periodic reactivity perturbations are involved.